Corporate-level strategy - Campbell, Andrew (Henry Stewart Talks, 2013)
Simple large company, The corporate parent, Portfolio strategy – Management or parenting strategy, Three reasons for investing in a business, Good business matrix, How important is growth, E.ON’s portfolio of businesses 2008, Ashridge portfolio display, Conditions for net added value, Direct guidance or help, Encourage/drive synergies, Create value at parent level, Ways to manage the group of businesses, How to design/re-design the parent, The size/role of the corporate center, Three elements of group strategy